(untitled) (Environment & Health, 2017)
Objective: We analyzed the methodological approaches to the control of drinking water radioactivity, rationalized functions and scopes of the action of various standards and methods. Material and methods: In the study of water we applied the various radiometric and spectrometric methods that satisfied the rules of sufficient selectivity and sensitivity that allowed to perform the limitation on the normalized value of radioactivity and / or dose. Results: Methodical approaches to the control of radioactivity of drinking water in Ukraine were analyzed. The priorities of the application of the requirements of NRBU-97, DSanPin 2.2.4-171-10, Directive 98/83 / EC on water radioactivity were differentiated. The algorithms of the studies for the fulfillment of the requirements of existing standards and features of the dissemination of mentioned standards were rationalized. Conclusions: Existing standards NRBU-97, State Sanitary Rules and Norms 2.2.4-171-10, concerning the radioactivity of drinking water, include or complement each other, and for the expansion of the scope of the Directive 98/83 /EC requirements in Ukraine, the corresponding changes in State Sanitary Rules and Norms 2.2.4-171-10 should be approved first of all.